2009
DOI: 10.1124/dmd.109.030775
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate Transporter-Mediated Transport of γ-Hydroxybutyric Acid in Human Intestinal Caco-2 Cells

Abstract: ABSTRACT:The objectives of this study were to determine mRNA expression of monocarboxylate transporters (MCT) and to evaluate intestinal transport of the MCT substrates ␥-hydroxybutyrate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…GHB and GBL are abused orally, and the oral absorption of high doses of GHB is dose-dependent in rats, with maximum plasma concentrations increasing less than proportionally with dose, indicating a saturable absorption process (Lettieri and Fung, 1979). Our in vitro studies in Caco-2 cells also indicate saturable transport of GHB, which is pH dependent and could be inhibited by MCT inhibitors (Lam et al, 2010). These studies suggest that, along with its concentration-dependent renal reabsorption, the dose-dependent oral absorption of GHB is also due to saturation of MCTs, which are present throughout the intestine in both rats and humans (Kirat et al, 2009;Merezhinskaya and Fishbein, 2009).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…GHB and GBL are abused orally, and the oral absorption of high doses of GHB is dose-dependent in rats, with maximum plasma concentrations increasing less than proportionally with dose, indicating a saturable absorption process (Lettieri and Fung, 1979). Our in vitro studies in Caco-2 cells also indicate saturable transport of GHB, which is pH dependent and could be inhibited by MCT inhibitors (Lam et al, 2010). These studies suggest that, along with its concentration-dependent renal reabsorption, the dose-dependent oral absorption of GHB is also due to saturation of MCTs, which are present throughout the intestine in both rats and humans (Kirat et al, 2009;Merezhinskaya and Fishbein, 2009).…”
Section: Introductionmentioning
confidence: 72%
“…L-lactate on high oral doses of GHB. Additionally, although we have demonstrated GHB to be a substrate of MCT1, MCT2, and MCT4, and demonstrated pH-dependent transport of GHB in kidney and intestinal cells (Wang et al, 2006;Wang and Morris, 2007a;Lam et al, 2010), GHB and L-lactate are also substrates for the sodium-coupled SMCT1(SLC5A8) (Cui and Morris, 2009), which is also present in rat intestine and kidney (Ganapathy et al, 2008). Further experiments may also be warranted to distinguish the contribution of MCTs and SMCTs to GHB transport and the effects of L-lactate at both physiologic sites.…”
Section: Treatment Of Oral Ghb/gbl Overdosementioning
confidence: 99%
“…In rats, this dose-dependence has been demonstrated to be due to saturable metabolism, saturable oral absorption, and saturable renal reabsorption (Lettieri and Fung, 1979;Arena and Fung, 1980;Morris et al, 2005). Saturable oral absorption and renal reabsorption have been explained by the concentration-dependent transport of GHB by monocarboxylate transporters (MCTs) (Morris et al, 2005;Wang et al, 2006;Lam et al, 2010). MCTs are proton-coupled transporters with ubiquitous expression, including expression at the intestine, kidney, brain, and at the red blood cell (RBC) membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it appears to be well tolerated in mice (no sign of sedation or abnormal behavior in the current studies). Robust synthetic routes to both HOCPCA and It has previously been reported that GHB is a substrate for MCT1, and the transporter is suggested to take part in the oral absorption and renal reabsorption of GHB, as well as GHB transport across the BBB (Bhattacharya and Boje, 2004;Wang et al, 2006;Lam et al, 2010). Given that GHB is a drug of abuse, for which no antidote is currently available, targeting MCT1-mediated transport holds great possibilities as a potential treatment strategy.…”
Section: Discussionmentioning
confidence: 99%